Genetic variability of ESAG6/7 gene Trypanosoma evansi - Dyah Haryuningtyas Sawitri; April H. Wardhana (Indonesian Center for Animal Research and Development (ICARD), 2017)
Trypanosoma evansi as an agent of Surra is one of the crucial parasitic diseases that cause great economic losses in Indonesia. These parasites need iron for growth and propagation phase which is obtained by receptor-mediated uptake of host transferin. The transferrin receptors are encoded by Expression Site Associated Genees (ESAGs). ESAG6/7 encodes transferrin receptors which reported have different affinities of a different host. The distinction of T. evansi pathogenicity is supposed to cause variability in the ESAG6/7 gene. This research was aimed to investigate the variability of genes ESAG6/7 T. evansi with different virulence in mice. This research was conducted in two steps: bioassay pathogeneicity in mice and analysis of ESAG6/7 gene sequences. The median survival time of mice was investigated after each group of mice infected by 25 T. evansi isolates from buffaloes where its geographically differ. The test results showed a difference of pathogenic virulence on 25 T. evansi isolates in mice. Sequence analysis of the ESAG6/7 gene from 25 T. evansi isolates origin from Indonesia tended to be homogeneous on the transferrin binding site but there was variability in the hypervariable site. These changes are able to separate high and low virulence of the T. evansi isolates. Phylogenetic tree analysis was formed 11 clades of 25 T. evansi. High virulence T. evansi was included in clades 7 and 10, while low virulence T. evansi was included in clade 5 and 11 and the moderate virulence was divided into those four clades.